Design for safety in construction in sub-Saharan Africa: a study of architects in Ghana. Issue 4 (3rd April 2021) - Manu, Patrick; Poghosyan, Anush; Agyei, Godfred; Mahamadu, Abdul-Majeed; Dziekonski, Krzysztof
Abstract: Design for safety (DfS) is an important mechanism for addressing accidents in construction. In the main, DfS studies have largely focussed on various regions of the world other than sub-Saharan Africa (SSA). Through a questionnaire survey, this study investigated the DfS awareness and practice among architects in the Ghanaian construction sector. Data analysis revealed that there is a low engagement in DfS practice despite a high level of awareness of DfS among architects. There is a high interest in DfS training juxtaposed against a low engagement in DfS training. DfS practice is not associated with: awareness of the concept of DfS; engagement in DfS professional development training; receipt of DfS education; membership of professional body; years of experience in role and the company size. Concerted efforts by industry stakeholders, including clients, educational institutions and design professional bodies would be required to encourage the application of DfS among architects and other design professionals within the Ghanaian construction environment. Furthermore, more studies on DfS within the SSA context are required in order to profile DfS awareness and practice among design practitioners and other industry stakeholders within the region.